Seed priming induces biochemical changes in melon plants and increase salt tolerance - Castañares, Jose Luis; Bouzo, Carlos Alberto (Ediciones INTA, 2020)
An experiment was conducted to evaluate the effect of priming on germination and initial growth of melon plants under salinity conditions. Two osmotic agents (NaCl and CaCl2) and two treatment durations (2 and 4 days) were compared. Germination percentage and growth of seedlings were evaluated at electrical conductivity 8.0 dS m-1. Total chlorophyll content, relative water content, root viability, proline content, relative electrolyte leakage, malondialdehyde concentration, peroxidase and catalase activity, Na+/K+ ratio in green parts, and K+ leakage from roots were measured. The best germination was obtained when seeds were soaked either with NaCl or CaCl2 for two days. Priming improved growth parameters and plants presented a better response in all the evaluated biochemical parameters. Results suggest that priming could be used to improve the performance of seeds and seedlings in situations of high salinity.